To solve the system of equations, we can use the method of substitution or elimination.
We'll use the method of elimination.
First, let's multiply the first equation by 4 and the second equation by -1 to cancel out y:
-36x + 4y = 48
-2x - 4y = 28
Now, let's add the two equations:
-36x + 4y + (-2x) - 4y = 48 + 28
-38x = 76
x = -2
Now, substitute the value of x into one of the original equations to solve for y.
-9(-2) + y = 12
18 + y = 12
y = 12 - 18
y = -6
So, the solution to the system of equations is x = -2 and y = -6.
Solve the system of equations
-9x+y=12
2x+4y=-28
1 answer